2013
DOI: 10.2967/jnumed.113.121020
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Specific Translocator Protein Signal of 18F-PBR111 in Healthy Humans: A Genetic Polymorphism Effect on In Vivo Binding

Abstract: PET is used to image active inflammatory processes by targeting the translocator protein (TSPO). In vitro, second-generation TSPO radioligands, such as PBR111, have been shown to bind to human tissue samples with either high affinity (high-affinity binders, HABs), low affinity (low-affinity binders, LABs), or an intermediate, mixed affinity (mixed-affinity binders, MABs). We previously explained these differences in affinity in human tissue via the rs6971 polymorphism in the TSPO gene and predicted that the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 30 publications
(49 reference statements)
5
86
0
Order By: Relevance
“…The procedure used to generate the metabolite corrected plasma input function has been described previously. 10 In brief, the total plasma curve was generated by multiplying the whole blood curve by plasma-over-blood ratio, and the parent fraction data were fitted to a sigmoid model:…”
Section: Preparation Of [ 11 C]pbr28mentioning
confidence: 99%
“…The procedure used to generate the metabolite corrected plasma input function has been described previously. 10 In brief, the total plasma curve was generated by multiplying the whole blood curve by plasma-over-blood ratio, and the parent fraction data were fitted to a sigmoid model:…”
Section: Preparation Of [ 11 C]pbr28mentioning
confidence: 99%
“…A 2-tissue-compartment kinetic model with a metabolite-corrected plasma input function was applied to the dynamic PET data using a fixed blood volume correction of 5% (19). For each VOI examined, the total volume of distribution (V T ) was estimated from the rate constants as described previously (22).…”
Section: Imaging Methodsmentioning
confidence: 99%
“…A recent study showed increased 18 F-PBR111 uptake corresponding specifically to activated microglia in experimental autoimmune encephalomyelitis (18). We have developed a robust approach for quantitative in vivo assessment of specific 18 F-PBR111 binding to TSPO (19).…”
mentioning
confidence: 99%
“…and [(18)F]-FEPPA for imaging brain inflammation have been linked to this polymorphism (88,(93)(94)(95)(96). However, structural analyses have shown that A147T TSPO is able to retain the same structural profile as the wild-type protein, and binds the first generation TSPO ligand, PK 11195, with comparable affinity (97).…”
Section: Complications In the Application Of Certain Tspo Pet Ligandsmentioning
confidence: 99%
“…Future follow on studies could therefore focus to assessing susceptibility in standard stress models of diseases where TSPO has already been linked to, for example, LPS-induced inflammation, ischemia-reperfusion injury, radiation/chemical-induced cancers, overfeeding or bacterial/viral infection. Nonetheless, age-related studies should also be recommended based on the brain-imaging evidences lately produced (96).…”
Section: Tspo -/-Knockout Mice: New Insights Of An Old Functionmentioning
confidence: 99%